Avaliação da viabilidade técnica e econômica da produção de biogás a partir de resíduo do processamento industrial de vegetais - Arruda, Heder Jobbins de (2020)
The replacement of fossil energy sources by renewable energy is a constant concern. The demand for ready-to-eat or fast-prepared products has increased and companies operating in this field have faced an increase in energy consumption and the generation of environmental liabilities. The industrialization of vegetables generates a large amount of organic waste such as peel, pulp, inedible parts of the plant and wastewater from the process. Thus, it is necessary to properly dispose of these residues, in accordance with current legislation and reducing the impact on the environment. Biodigestion or anaerobic digestion is a process that in addition to stabilizing organic compounds generates biogas, a fuel gas basically composed of CH4 and CO2, and a new biomass, liquid/solid material that can be used as a biofertilizer. The objective of this work is to verify the technical and economic feasibility of anaerobic digestion of vegetable processing waste from an industry in the state of Paraná aiming at energy production with biogas and the proper disposal of solid waste. To meet the objective, the residues with the theoretical potential for conversion to methane were identified, physicochemical analyzes were performed to characterize important aspects in biodigestion, the maximum biochemical potential of methane in the residue was verified using the VDI 4630 methodology and estimated the financial return that can be obtained from energy production. It was possible to verify a similar theoretical potential among the vegetal residues, and thus, the seasonality of the production does not significantly affect the biodigester performance. The potato processing residue was selected because it represents almost all of the waste generated for industry, and it had a C:N ratio of 42,04, an VS content of 8.68% and a pH of 7,33. In the Biochemical Biogas Potential test, an accumulated production of 615 L/kgVS was obtained in 31 days, and on the fifteenth day it reached 600 L/kgVS, with an average of 50,89% of methane. The best use of this volume of biogas observed is to replace the CNG and LPG fuels consumed in the industrial unit itself. By-products such as carbon dioxide and biofertilizer, or even biogas itself, may be negotiated in partnership with producers in the region.